Вплив тіолових антиоксидантів на вміст стрес-білка HSP70 у гіпокампі монгольських піщанок з гострою ішемією головного мозку - Павлов, Сергій Васильович; Pavlov, S. V. (My University, 2012)
In experiment on the model of acute cerebral ischemia was shown thiol antioxidants ability to influence on the stress-proteins HSP70 synthesis in hippocampus. Administration of the Tiotriasolin (50 mg/kg), Emoxipine (100 mg/kg), Mexidol (50 mg/kg) leads to the significant decrease of the cytotoxic marker of the oxide injury of the proteins – nitrotirosine, and to the increase of the HSP70 concentration. Comparative characteristics of the mentioned drugs showed statistically significant advantage of the Tiotriasolin.
Thiol antioxidants influence on the stress-protein HSP70 in hippocampus of the meriones unguiculatus with acute cerebral ischemia
Keywords: тіолові антиоксиданти; стрес-білок HSP70; ішемія головного мозку; thiol antioxidants; stress-proteins HSP70; acute cerebral ischemia